The narratives of Uruguayan exiled children not returned: an exile told in the first person (Clepsidra - Interdisciplinary Journal of Memory Studies, 2023)
This article tries to account for a new subject that emerges within the framework of the narratives of the Uruguayan post-dictatorship -but outside the borders of Uruguay- in a place little visited by the social sciences: the non-return from exile. A space of experience, but also of identity, where a subject arises that is read as "invisible" within the dominant narrative of the post-dictatorship. Not seeing herself in that story, or anywhere else, she becomes aware of her own non-existence and, in that act of self-reflexivity about herself and her past, she constitutes herself as an unreturned exiled daughter. A name -and a sociological category- that embodies daughters and sons born in Uruguay, exiled during their childhood or adolescence and who, at least permanently, have not returned to their country of origin. Some actors who, from the non-return, weave some narratives where the protagonists of exile are no longer the parents, but the children.
Keywords: Exile, Children, Non-Return, Identity, Narratives, Uruguayan Dictatorship